New Sycoracinae (Diptera, Psychodidae) from southern Brazil - Santos, Claudiney Biral Dos; Bravo, Freddy; Falqueto, Aloísio (Zootaxa, 2013)
Two new species of Sycorax from the Atlantic Rain Forest of Espírito Santo, Sycorax canaanensis Santos, Bravo & Falqueto sp. nov. and Sycorax tuberculata Santos, Bravo & Falqueto sp. nov. are described and illustrated. Male speci-mens were collected with CDC light traps in the Biological Reserve of Augusto Ruschi, municipality of Santa Teresa, state of Espírito Santo, Brazil. This finding raises the number of described Western Hemisphere Sycorax species to 15.